INTERTWINEMENT: THE MODALITIES OF THE UNGRASPABLE - KUCHTOVA, Alzbeta (Studia Universitatis Babeș-Bolyai Philosophia, 2023)
The aim of this paper is to accentuate the distinction between the ineffable, the unrepeatable and the conceptually ungraspable. These are to be considered as three modalities of the ungraspable language that enable us to understand Derrida’s attitude to negative theology. While he distanced himself from an apophasis of negative theology Comment ne pas parler. Dénégations, in Différance he stated that différance is not a concept, not a word – it is an inexpressible. Therefore, there are at least three modalities of “ungraspable” language: “inexpressible,” “conceptually ungraspable,” “unrepeatable” as non-iterable. This paper is a translation of this text originally published in Slovak language: Kuchtova, A., „Prelínanie. Modality neuchopiteľného,” Filosofický časopis, vol. 68, n. 2, pp. 259-270.